Monte Carlo simulations of out‐of‐field skin dose due to spiralling contaminant electrons in a perpendicular magnetic field. Issue 3 (14th February 2019) - Malkov, Victor N.; Hackett, Sara L.; van Asselen, Bram; Raaymakers, Bas W.; Wolthaus, Jochem W. H.
Abstract : Purpose: The purpose of this study was to evaluate the potential skin dose toxicity contribution of spiralling contaminant electrons (SCE) generated in the air in an MR‐linac with a 0.35 or 1.5 T magnetic field using the EGSnrc Monte Carlo (MC) code. Comparisons to experimental results at 1.5 T are also performed. Methods: An Elekta generated phase space file for the Unity MR‐linac is used in conjunction with the EGSnrc enhanced electric and magnetic field transport macros to simulate surface dose profiles and depth‐dose curves in panels located 5 cm away from the beam edge and positioned either parallel or perpendicular to the magnetic field. Electrons generated in the air will spiral along the magnetic field lines, and though surface doses within the field will be reduced, the electrons can contribute to out‐of‐field surface doses. Results: Surface dose profiles showed good agreement with experimental findings and the maximum simulated doses at surfaces perpendicular to the magnetic field were 3.77 ± 0.01% and 3.55 ± 0.01% for 1.5 and 0.35 T. These results are expressed as a percentage of the maximum dose to water delivered by the photon beam. The surface dose variations in the out‐of‐field region converge to the 0 T doses within the first 0.5 cm of material. An asymmetry in the dose distribution in surfaces positioned on either side of the photon beam and aligned parallel to the magnetic field is determined to be due to the magnetic field directing electrons deeper into, or localizing them to the surface of, the measurement panel. Conclusions: These results confirm the SCE dose contribution in surfaces perpendicular to the magnetic field and show these doses to be of the order of a few percentage of the maximum dose to water of the beam. Good agreement in the dose profiles is seen in comparisons between the MC simulations and experimental work. The effect is apparent in 0.35 and 1.5 T magnetic fields and dissipates within the first few millimeters of material. It should be noted that only SCEs from beam anteriorly incident on the patient will influence the patient surface dose, and the use of beams incident over different angles will reduce the dose to any particular patient surface.